Is Patience Malleable via Educational Intervention? Evidence from Field Experiments - Tim Kaiser; Lukas Menkhoff; Luis Oberrauch (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the malleability of patience via educational interventions by aggregating evidence from earlier experiments in a meta-analysis and by conducting a field experiment. We find that the average effect of interventions on patience is positive but uncertain. The age of students explains a large share of between-study heterogeneity in treatment effects. Thus, we conduct a field experiment covering both youths and adults in Uganda. We find heterogenous effects by age: adults' patience measured in incentivized tasks is unaffected by the intervention after 15 months follow-up, but we observe large effects on patience and estimated discount factors for youth.
Keywords: C93; D15; I21; 330; patience; time preferences; malleability; field experiment; educational intervention